Multimodal didactic sequence for energy teaching: an experience with deaf included and the use of new signs-terms (Research, Society and Development, 2022)
The deaf are clothed and made to exist essentially through visual experiences. Thus, it is coherent to think of a pedagogy based on the visual as an appropriate resource because it essentially represents what belongs to the visual order. When it comes to communicating chemical knowledge, the use of visual resources and different semiotic modes is essential for the teaching and learning process. Furthermore, the appropriate use of the various modes (multimodality) helps the student's cognition and expands their understanding and perception of certain knowledge in question. Thus, through this article, we aim to share an action research regarding the experience of a multimodal didactic sequence - elaborated with deaf people and validated in a classroom with two deaf people included - for teaching different types of energy manifestations. At that time, it was also possible to evaluate the use of new term signs in Brazilian Sign Language (Libras) for the terminologies SOUND ENERGY, LIGHT ENERGY, CHEMICAL ENERGY and ELECTRIC ENERGY. The validation of the teaching sequence showed that the strategies that enhance the culture and the visual way of learning for the deaf, that value dialogic moments and that intensely explore the multimodalities in the construction of knowledge are important in working with these included students, and these same resources, are also essential for reaching the diverse students of a classroom.